Cation‐assisted adsorption of chlorophenols by nano‐xerogels. (20th October 2015) - Hassani, Sorour; Ghasemi, Awat; Fazli, Mostafa; Haghbeen, Kamahldin; Legge, Raymond L.
Abstract : With water quality deteriorating globally, identification of novel adsorbents for removal of chloroaromatic compounds for wastewater treatment is of growing interest. Classic xerogels produced by drying sol‐gels of tetraalkoxy silanes, such as tetramethoxy orthosilane (TMOS) or tetraethoxy orthosilane (TEOS), carry a negative surface charge in water when the pH is higher than the Point of Zero Charge (PZC). This feature was employed in this study to load divalent metal cations on the surfaces of these materials to facilitate chlorophenol (CP) adsorption. Although classic xerogels do not show a high affinity for the adsorption of chlorophenols such as 2‐chlorophenol (2CP) in aqueous media, TEOS xerogels loaded with the cations Ni 2+, Cd 2+, and Zn 2+ showed 225, 249, and 306 % increases, respectively, in the adsorption of 2CP compared to the unloaded TEOS xerogel. Adsorption of the divalent cations on the xerogels exhibited the order of Zn 2+  > Cd 2+  > Ni 2+, with maximum adsorption capacities (Q°) of 15.9 and 13 mg/g for Zn 2+ on TEOS and TMOS xerogels, respectively. Using TEOS xerogels loaded with Zn 2+ (TEOS‐Zn), adsorption of 2CP, 2, 4‐dichlorophenol (DCP), and 2, 4, 6‐trichlorophenol (TCP) in aqueous media was studied. The adsorption was found to be spontaneous and obeyed pseudo‐second order kinetics, suggesting a chemisorption mechanism between CP and TEOS‐Zn. The equilibrium isothermal adsorption data were most closely fitted with a Langmuir equation resulting in Q° values of 13.9, 9.17, and 8.5 mg/g for 2CP, DCP, and TCP, respectively.